Perception of Shea Nut Tree as an Economic Tree among Farmers in Oyo State, Nigeria - Rasheed Gbolagade Adeola (International Journal of Agricultural Management and Development, 2012)
The importance of shea tree to the people of south-westernNigeria cannot be over emphasized considering both theeconomic and environmental uses of the tree. However, effortshave not been made to propagate its production by the farmersas the shea tree still grows in the wild state. It would beworthwhile to investigate farmers’ perception of shea nut tree asan economic tree and their attitudes toward the conservationmeasures needed to prevent its extinction. Multi-stage samplingtechnique was used to select 160 farmers for the study. Astructured interview schedule was used to collect data from therespondents. Descriptive statistics of means and percentageswere used to describe the data while correlation coefficientswere employed to determine the relationships that exist betweenfarmers’ perception and their socio- economics characteristics.A larger percentage of the farmers claimed the awareness of thepotential products of shea nut trees. Majority (90.6%) of the respondentsperceived shea tree as an economic tree and indicatedthat it provides income for women and children that gather thefruits. Most of the farmers had favourable attitude toward shea nuttree as an economic tree. Land ownership status (r = 0.536), age(r = 0.875), education (r = 0.725), farming experience (r = 0.508),household size (r = -0.817) and farm size (r = -0.673) hadsignificant influence on the perception of farmers. The studytherefore recommends that the extension agencies should playsignificant role in educating the farmers on the importance ofconserving the trees to sustain its economic benefits.